PP.17.07: FIRST MEASUREMENT BLOOD PRESSURE OVERSTIMATED RESULTS. (June 2015) - Lopez-Rivera, J.; Scrocchi, S.; Lopez, S.; Suarez, F.; Pereira, E.
Abstract : Objective: Arterial hypertension is the main risk factor attributable to cardiovascular morbidity and mortality. In population, studies have shown that there are a linear and continuous correlation between the increase blood pressure (BP) and risk of a coronary event, stroke, heart failure, renal failure. Most epidemiological studies in concentrated human groups have based hypertension with the first BP measurement, even though guidelines require at least two, for diagnosis of hypertension, however this is obviated by the number of people that such studies should be done. Leaving a second take on another occasion to patients whose numbers was increased, losing at least 20% of the surveyed population. Is also known that human group's agglomerates may have a greater possibility of white coat hypertension phenomenon. Design and method: Under this, cross-sectional study was conducted in a mall, where prior knowledge informed people are taking their blood pressure (BP), on 2 occasions, with a difference of five minutes between the two measurements, in order to classifying the population as hypertensive or normotensive if BP was equal to or greater than 140/90 mm Hg or less respectively, and evaluate BP between the first and second take, both systolic and diastolic component, auscultatory and oscillometric. It was used an statistical analysis package software SPS 19, and Student t test was performed for parametric variables correlated with a confidence interval of 95%. Results: 151 people were surveyed, 56.96% women and 43.04% men, mean age of 52.62 years, range between 18–81 years, 51.3% had no regular employment, 46% did not own housing and 62% had secondary and university education. The prevalence of hypertension using the first measurement blood pressure was 40.3% and after the second was 38.9%, In the graph the relationship between the average systole / diastolic 1st and 2nd BP measurement are shown, auscultatory and oscillometric. Figure. No caption available. Conclusions: The first measurement of systolic and diastolic blood pressure using the auscultatory or oscillometric method over estimated in the general population blood pressure, so it is necessary to perform a second take to minimize this pressor effect of alert.